2009
DOI: 10.1016/j.bone.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-associated osteonecrosis of the jaw: A key role of inflammation?

Abstract: Osteonecrosis of the jaw (ONJ) can be associated with nitrogen-containing bisphosphonates (NBPs) therapy. Various mechanisms of NBP-associated ONJ have been proposed and there is currently no consensus of the underlying pathogenesis. The detailed medical and dental histories of 30 ONJ patients treated with NBPs for malignant diseases (24) or osteoporosis (6) were analyzed. The necrotic bone was resected and analyzed histologically after demineralization. In 10 patients the perinecrotic bone was also resected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
144
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 51 publications
17
144
2
6
Order By: Relevance
“…However, histological studies of tissue removed from patients with ONJ have demonstrated the presence both of osteoclasts and bone resorption. Lesclous et al [59] reported the presence of TRAP-positive mononuclear and multinucleate cells in perinecrotic tissue, and in other studies, the presence of increased numbers of osteoclasts and active bone resorption have been reported. Furthermore, isotope studies using technetium-labelled diphosphonate or F-18 FDG PET have shown increased uptake in the regions surrounding the necrotic jaw [60][61][62][63].…”
Section: Suppression Of Bone Turnovermentioning
confidence: 97%
See 2 more Smart Citations
“…However, histological studies of tissue removed from patients with ONJ have demonstrated the presence both of osteoclasts and bone resorption. Lesclous et al [59] reported the presence of TRAP-positive mononuclear and multinucleate cells in perinecrotic tissue, and in other studies, the presence of increased numbers of osteoclasts and active bone resorption have been reported. Furthermore, isotope studies using technetium-labelled diphosphonate or F-18 FDG PET have shown increased uptake in the regions surrounding the necrotic jaw [60][61][62][63].…”
Section: Suppression Of Bone Turnovermentioning
confidence: 97%
“…However, histological studies of affected tissue from patients with ONJ have generally shown the presence of normal vasculature [59,69], and furthermore, there is no evidence that denosumab has effects on angiogenesis. ONJ has been described in a few patients treated for cancer with bevacizumab, an antiangiogenic agent that targets VEGF and is used in the treatment of advanced metastatic disease.…”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…1 It will be important to clarify whether zoledronate-mediated NK cell activation, as reported here, can contribute to the development of osteonecrosis of the jaw, which can be considered an inflammatory condition associated with substantial leukocyte infiltration. 48 Infiltrating leukocytes may encounter high concentrations of bisphosphonate, which have been shown previously to accumulate in the resorption space, where they may reach 0.1-1mM. 49 In summary, we have shown that the potent bisphosphonate zoledronate not only induces ␥␦ T-cell activation but can also induces NK cell activation.…”
Section: Discussionmentioning
confidence: 97%
“…Several types of inflammatory reactions have been observed in patients treated with NBPs, including flu-like symptoms, esophageal irritation, and osteonecrosis of the jaw (2). These side effects might be attributable to the immune-modulating effects of NBPs (3). Inhibition of the mevalonate pathway by NBPs causes isopentenyl-5-pyrophosphate accumulation in monocytes, augmenting γδ T-cell activation in vitro (4), but additional effects likely contribute to the in vivo inflammatory responses to NBPs (1).…”
mentioning
confidence: 99%